Amalan pengurusan masa murid sekolah menengah selepas waktu sekolah dan hubungannya dengan pencapaian akademik - Ismail, L.; Selvaraj, V.; Mohd Salleh, N.; Darusalam, G. (2011)
The purpose of this study is to understand the time used by secondary school students after school and its relationship with academic achievement. A total of 604 respondents consisting of Form One to Form Five students from two secondary schools in Kinta District, Perak were selected. Questionnaire forms were used to collect data for this quantitative type of study. The findings show that the secondary school students have nine categories of activities after school hours. The student’s daily or weekly time use have almost a similar pattern but varies a little in terms of time proportioning. The respondents perceive that they are the decisions makers on which type of activity to choose after school hours, followed by parents, peer group, mass media and teachers. Overall, the respondents have set their goals in their selection but have less commitment to fulfil their goals. Time used after school also varies according to gender, age, location of their home, and race. The findings show that all the activities being done after school have weak correlation or no correlation with academic achievement. Nevertheless, the findings show that only academic orientated activities such as learning, revision and attending tuition have a significant relation with academic achievement.